Geopolitical and Geoeconomic Value of Access to Sea Resources: The Case of the Land-locked States in Africa - Siousiouras, Petros (The International Hydrographic Review, 2005)
The issue of the African Landlocked States (ALS) is of critical importance both for their own developmental course but also for the future of the whole African continent as well. During the period of decolonisation the ALS took several initiatives culminating in the Third UN Convention for the Law of the Sea, which legally resolved a large number of their problems concerning access to the sea. Despite that fact economic development is still questionable. What seems to be needed is a wider development-planning programme that would involve several regional development programs with the participation of the business world and the private sector.